2021
DOI: 10.13031/trans.14246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sunlamp-Based Lighting Mode on Growth Performance, Survival Rate, Stress Response, and Oxidative Stress of Juvenile Chinese Soft-Shelled Turtles (Pelodiscus sinensis)in a Greenhouse

Abstract: HighlightsSunlamps with UV and visible light were used in large-scale farming of Chinese soft-shelled turtles in a greenhouse.The effects of lighting mode on the growth performance, survival rate, stress response, and oxidative stress of juvenile Chinese soft-shelled turtles were studied.Lighting mode had significant impacts on survival rate, stress, and oxidative stress of Chinese soft-shelled turtles.Lighting the basking area only was the optimal lighting mode and caused less stress for Chinese soft-shelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Furthermore, the regulatory role of B cells is not well understood. A study of desert tortoises suggests that B cells play a role in polarizing the immune system to avoid a dangerous inflammatory response [158]. This study suggests that B cells play a role in controlling inflammation.…”
Section: Humoral Immunitymentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, the regulatory role of B cells is not well understood. A study of desert tortoises suggests that B cells play a role in polarizing the immune system to avoid a dangerous inflammatory response [158]. This study suggests that B cells play a role in controlling inflammation.…”
Section: Humoral Immunitymentioning
confidence: 90%
“…However, reptiles' responses are long-lasting responses with antibodies detectable up to 34 weeks postimmunization [115]. It is suggested that the longer-lasting NAb response in reptiles is a 'trade-off' when T cell proliferation is diminished due to seasonal changes of the spleen and thymus [67,158].…”
Section: Natural Absmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the effects of light on turtles have been reported in several studies. For instance, the effect of light pollution on the nesting and the population of hatching turtles [22][23][24][25] , the effect of ultraviolet radiation on the 25-hydroxyvitamin D3 of turtles [26,27] and the effect of lighting mode on Chinese soft-shelled turtle [28] . Although the optimal lighting mode for the Chinese soft-shelled turtle has been studied, the impact of lighting mode on Chinemys reevesii cultured indoors is still little known.…”
Section: Introductionmentioning
confidence: 99%